Analisis Perkembangan Norma Internasional “War on Terror” dalam Perspektif Realis, Liberalis dan Konstruktivis - Ardli Johan Kusuma; Tulus Warsito; Surwandono Surwandono; Ali Muhammad; Ulung Pribadi (Universitas Diponegoro, 2019)
This paper discusses about the dynamics of the development of the international norm “war on terror” which is analyzed from three dominant approaches in international relations; realism, liberalism, and constructivism. Specifically, this paper seeks to reveal the dynamics of war on terror norms from its inception to date, where the norms have been adopted by the majority of the international community. The first stage is the emergence of the norms which fall within realist thinking stressing on materialist and rationalist dimensions such as security issues and threats from terrorists. The second stage emphasizes on the role of international organizations and international law that closely associated with liberalist thinking. The last stage is strengthening the norms focusing on shared ideas related to humanity, human rights and freedom to build a common identity that led to the emergence of the counter-terrorism norms that fit constructivist perspective.